An Innovative and Conservative Approach to Molar Distalization - Revathi Peddu; Kalyani Mallavarapu; Ashok Kumar Talapaneni; Aruna Dokku (Wolters Kluwer Medknow Publications, 2024)
Nonextraction approach in correcting Class II malocclusion has gained a lot of attention over the past few years. Clinicians prefer intraoral appliances as compared to extraoral appliances to achieve distal molar movement; the reason being intraoral appliances depends minimally on patient cooperation. In this article, a case report was presented in which a patient was treated with modified rapid maxillary expander, a concept designed from Veltri distalizer considering its advantages. Molar distalization of 4 mm was achieved with minimal anchorage loss on premolars and anteriors. Class I molar, canine relation was achieved with 2 mm of overjet and overbite. Modified appliance when used at appropriate timing was found to be an effective and conservative approach in distalization of maxillary first molars.